Kandungan Bakteri Sulfur Pada Tekstur Tanah Tambak Sungai Bendera Dusun Kenyamukan Desa Sangatta Utara - Supiarni, Supiarni; Haryasakti, Anshar; Azhar, Moh Saiful (Sekolah Tinggi Pertanian Kutai Timur, 2015)
The research was conducted in March-April 2014, at third ponds in the Bendera River, North Sangatta Village, This research used descriptive method, samples were analyzed in the Labratory of Fisheries and Marine Science of Mulawarman University ad identify relationship between variabel data was obtained regression analysis with SPSS software of descriptive analysis presented in the form of tabels and graphs. The research result was indentified total populations of sulfur bacterial colonies obtained at first station ranges form 4,35 x 104 log CFU/g to 6,98 x 106 log CFU/g samples with an average 6,51 x 106 log CFU/g samples with percentage of 42% silt, 20% clay, and 38% sand, then second ranges station from 5,58 x 105 log CFU/g to 7,50 x 107 log CFU/g samples with an average 7,21 x 107 log CFU/g samples with percentage of 31% silt, 13% clay, dan 56% sand, then the third station ranges from 4,70 x 104 log CFU/g to 5,91 x 107 log CFU/g samples with an average 5,52 x 107 log CFU/g samples with percentage 40% silt, 9% clay, dan 51% sand. The relationship between sulfur bacteria of dust partitions of anova was linearity meants there was influenced significant between sulfur bacteria with soil texture, moreove the clay and sand partitions not significant meants regression model did not criteria of linearity.